Experimental study on the seismic performance of concrete-filled steel tube columns with a multiple-chamber round-ended cross-section - Liu, Jing; Yu, Wenzuo; Fang, Yawei; Pan, Zimao (Frontiers in Materials, 2024)
Reinforced concrete bridge piers with round-ended sections are susceptible to bending, bending-shear, and shear failure after earthquakes in high-intensity areas, thus necessitating improved seismic performance. This study introduced a novel design for a concrete-filled steel tube (CFST) column, featuring a multi-chambered, round-ended cross-section. The use of longitudinal and transverse stiffeners divided the column section into distinct chambers, thereby enhancing the seismic performance of the columns. A total of 12 groups of static tests were performed to examine the effect of chamber layout, axial compression ratio, and aspect ratio on columns' hysteresis behavior, and the hysteresis curves, skeleton curves, failure modes, stiffness degradation, ductility, and energy dissipation capacity were obtained. Results demonstrated the favorable seismic performance of composite columns. Additionally, an increase in chambers led to a full hysteresis curve, enhancing bearing and energy dissipation capacities. The displacement ductility coefficient (μ) ranged between 3.88 and 7.45, and the 2 design parameters have minimal influence on the stiffness degradation of the composite beam.Based on the results, the long and short sides of the CFST columns with a large length-width ratio should be arranged to be relatively close in length.